Condition monitoring of rolling stock using wheel/rail forces - Palo, Mikael; Schunnesson, Håkan; Kumar, Uday (Luleå tekniska universitet, Drift, underhåll och akustik, 2012)
Railway vehicles are efficient because of the low resistance in the contact zonebetween wheel and rail. In order to remain efficient both train operators and infrastructureowners need to keep rails, wheels and vehicles in acceptable condition. Wheelwear affects the dynamic characteristics of vehicles and the dynamic force impact onthe rail.The shape of the wheel profile affects the performance of railway vehicles in differentways. Wheel condition has historically been managed by identifying and removingwheels from service when they exceed an impact threshold. Condition monitoring ofrailway vehicles is mainly performed using wheel impact load detectors and truck performancedetectors. These systems use either forces or stress on the rail to interpretthe condition.This paper will show measurements taken at the research station outside Luleå innorthern Sweden. The station measures the wheel/rail forces, both lateral and vertical,at the point of contact in a curve with 484 m radius at speeds up to 100 km/h. Dataare analyzed to show differences for various wheel positions and to determine therobustness of the system. Godkänd; 2012; Bibliografisk uppgift: CD-ROM; 20120823 (mikpal)